ANALYZING PRE-SERVICE ENGLISH TEACHER NEEDS IN DEVELOPING SOCIAL COMPETENCE IN 21st CENTURY - Hidayat, Hendi; Widianti, Widianti (STIT Buntet Pesantren Cirebon, 2022)
This research was conducted to analyze the needs of pre-service teachers in entering the field of education as a provision so that pre-service teachers can better prepare themselves and can find out how to become successful teachers. The researchers applied a qualitative case study approach. Data for analysis were collected from critical literature reviews and interviews. The focus mentioned in previous studies was not specifically directed at the needs of pre-service teachers. In this study, it is explained how to become a successful teacher in the 21st century and know the needs of social competence in the 21st century. The result shows that there are six indicators of social competence in the 21st and the needs for pre-service teachers are able to have every indicator of social competence. They are: (1) Reflecting inclusivity, objectivity and fairness, (2) Understanding how to communicating effeciently and effectively, (3) Having cultural sensitivity and knowing how to deal with diversity, (4) Contributing to the educational of development in schools, (5) Mastering ICT in order to increase educational quality, and (6) Having positive attitudes, behaviors, and ethics, as well as a clear sense of how to dress and speak the language.